Evaluation of non-invasive diagnostic tests for Mycoplasma pneumoniae pneumonia - Fan, Yongwei; Tan, Zhenyun; Wang, Zhenfa; Pan, Huaqin; Zhou, Jingrun; Yang, Jiong; Zhang, Guqin (Frontiers in Immunology, 2025)
BackgroundAccurate and timely identification of Mycoplasma pneumoniae pneumonia (MPP) remains a clinical challenge. Although nasopharyngeal swab nucleic acid testing (NAAT) and serum IgM antibody assays are widely used, their diagnostic performance varies across studies. This study aimed to retrospectively evaluate the sensitivity and specificity of the two non-invasive methods (NAAT and serum IgM antibody assays) for MPP in real-world clinical settings.MethodsWe conducted a retrospective study of adult patients hospitalized for community-acquired pneumonia (CAP) from January 2024 to October 2024. All enrolled patients underwent bronchoalveolar lavage fluid metagenomic next-generation sequencing (BALF-mNGS) and had received at least one of two non-invasive tests (NAAT or serum IgM antibody assays). The sensitivity and specificity of NAAT and serum IgM antibody assays were calculated against the final diagnosis. A non-inferiority test was used to determine whether the sensitivity of NAAT or serum IgM antibody assays was not inferior to that of mNGS.ResultsAmong 594 patients included in the analysis, 60 were diagnosed with MPP based on a composite reference standard that included laboratory testing results and adjudication by two senior clinicians in accordance with clinical and radiological findings. The sensitivity and specificity of NAAT were 74.1% and 99.3%, respectively, while those of serum IgM antibody assays were 23.6% and 98.0%. McNemar’s test revealed a statistically significant difference in sensitivity between mNGS and the two non-invasive tests (NAAT and serum IgM antibody assays) (P<0.05). The non-inferiority analysis revealed that both NAAT (sensitivity difference: -24.2%, 95% CI: -36.1 to -12.1%; P<0.01) and serum IgM antibody assays (-76.5%, 95% CI: -96.6 to -56.3%; P<0.01) failed to meet the 10% non-inferiority margin compared to mNGS.ConclusionIn clinical practice, a positive result from either NAAT or serum IgM antibody assays can serve as reliable adjunct evidence for diagnosing MPP. However, in cases with a high clinical suspicion of MPP, negative results from both methods are not sufficient to rule out the diagnosis. For MPP, mNGS remains the most effective diagnostic method compared to non-invasive testing alternatives.